Is implementation of a hospital pathway for high‐flow nasal cannula initiation and weaning associated with reduced high‐flow duration in bronchiolitis?. Issue 12 (15th September 2022) - Tarantino, Laura; Goodrich, Nathaniel; Kerns, Ellen; McCulloh, Russell; Burrows, Jason
Abstract: Background: High‐flow nasal cannula (HFNC) therapy is widely used for children with bronchiolitis, but its optimal role remains uncertain. Our institution created and later revised a clinical pathway guiding HFNC initiation and weaning. Methods: A retrospective review of 1690 bronchiolitis encounters was conducted. Trends in the duration of HFNC and hours spent weaning HFNC as proportions of the monthly hospital length of stay (LOS) for bronchiolitis, hospital LOS, and escalation of care were compared using interrupted time series (ITS) models across three study periods: Baseline (HFNC managed at provider discretion), Intervention 1 (pathway with initiation at 0.5 L/kg/min and escalation up to 2 L/kg/min), and Intervention 2 (revised pathway, initiation at the maximum rate of 2 L/kg/min). Both pathway iterations provided titration and weaning guidance. Maximum respiratory scores were used to adjust for case severity. Results: After adjustment for severity and time, both HFNC duration and HFNC weaning time (as a proportion of monthly LOS) decreased at the start of Intervention 1, but subsequently increased. During Intervention 2, both these measures trended downward, returning to baseline. Total LOS did not change in the baseline or intervention periods. Escalation of care did not differ from baseline to the end of Intervention 2. Conclusion: Initiating HFNC at higher flow rates with weaning guidance for children hospitalized with bronchiolitis was associated with a reduction in HFNC duration without differences in LOS or escalation of care. These findings suggest that standardization through clinical pathways can limit HFNC duration in bronchiolitis.